The progress and prospect of natural components in rhubarb (Rheum ribes L.) in the treatment of renal fibrosis - Wang, Yangyang; Yu, Fangwei; Li, Ao; He, Zijia; Qu, Caiyan; He, Caiying; Ma, Xiao; Zhan, Huakui (Frontiers in Pharmacology, 2022)
Background: Renal fibrosis is a key pathological change that occurs in the progression of almost all chronic kidney diseases . CKD has the characteristics of high morbidity and mortality. Its prevalence is increasing each year on a global scale, which seriously affects people’s health and quality of life. Natural products have been used for new drug development and disease treatment for many years. The abundant natural products in R. ribes L. can intervene in the process of renal fibrosis in different ways and have considerable therapeutic prospects. Purpose: The etiology and pathology of renal fibrosis were analyzed, and the different ways in which the natural components of R. ribes L. can intervene and provide curative effects on the process of renal fibrosis were summarized. Methods: Electronic databases, such as PubMed, Life Science, MEDLINE, and Web of Science, were searched using the keywords ‘R. ribes L.’, ‘kidney fibrosis’, ‘emodin’ and ‘rhein’, and the various ways in which the natural ingredients protect against renal fibrosis were collected and sorted out. Results: We analyzed several factors that play a leading role in the pathogenesis of renal fibrosis, such as the mechanism of the TGF-β/Smad and Wnt/β-catenin signaling pathways. Additionally, we reviewed the progress of the treatment of renal fibrosis with natural components in R. ribes L. and the intervention mechanism of the crucial therapeutic targets. Conclusion: The natural components of R. ribes L. have a wide range of intervention effects on renal fibrosis targets, which provides new ideas for the development of new anti-kidney fibrosis drugs.